Correlation of dynamic contrast-enhanced MRI and diffusion-weighted MR imaging with prognostic factors and subtypes of breast cancers - Chen, Hui; Li, Wei; Wan, Chao; Zhang, Jue (Frontiers in Oncology, 2022)
Objective: To determine the preoperative MRI findings of breast cancer on dynamic contrast- enhanced MR imaging and diffusion-weighted MR imaging in different molecular subtypes . Materials and Methods: A retrospective study was conducted for 116 breast cancer subjects who underwent preoperative MRI and surgery or biopsy. Three radiologists retrospectively assessed morphological and kinetic characteristics on DCE-MRI and tumour detectability on DWI, by using apparent diffusion coefficient (ADC) values of lesions. Clinicopathologic and MRI features of four subtypes were compared. The correlation between clinical and MRI findings with molecular subtypes were evaluated using Chi-square and the ANOVA test, while the Mann-Whitney test were used to analyze the relationship between ADC and prognostic factors. Results: 116 women diagnosed with breast cancer confirmed by surgery or biopsy, subtypes of breast cancer as following: Luminal A (27, 23.3%), Luminal B (56, 48.2%), HER2 positive (14, 12.1%), and triple negative (19, 16.4%) respectively. Among subtypes, significant differences were found in axillary node metastasis, histological grade, tumor shape, rim enhancement, margin, lesion type, intratumoral T2 signal intensity, Ki-67 index and paratumoral enhancement (p<0.001, p< 0.001,p<0.001,p<0.001,p<0.001,p<0.001,p<0.001,p<0.001,p=0.02.respectively).On DWI, mean ADC value of TNBC (0.910×10−3 mm2/s) was lowest compared to luminalA (1.477×10−3 mm2/s), luminalB (0.955×10−3 mm2/s) and HER2 positive (0.996×10−3 mm2/s) (P < 0.001). Analysis of the correlation between different prognostic factors and ADC value showed that only axillary lymph node status and ADC value had a statistically significant difference (P=0.009). Conclusion: Morphologic features of MRI can be used as imaging biomarkers to identify the molecular subtypes of breast cancer. In addition, quantitative assessments of ADC values on DWI may also provide biological clues about molecular subtypes.